C1q/TNF-related protein 1 links macrophage lipid metabolism to inflammation and atherosclerosis. (July 2016) - Wang, Xiao Qun; Liu, Zhu Hui; Xue, Lu; Lu, Lin; Gao, Jie; Shen, Ying; Yang, Ke; Chen, Qiu Jing; Zhang, Rui Yan; Shen, Wei Feng
Abstract: Background and aims: Macrophage is a major contributor to the development of atherosclerosis by taking up deposited lipoprotein and eliciting local inflammation. Previously, we and others have shown C1q/TNF-related proteins (CTRPs) play diverse roles in vascular functions. In this study, we sought to investigate the changes in CTRP expression levels during vital biological processes in macrophages and their relation to inflammatory responses. Methods: Western blot and real-time PCR were performed to analyze CTRPs expression levels in human peripheral blood mononuclear cells, primary macrophages and lipid-laden foam cells. Mechanisms that regulate CTPR1 expression were further investigated by bioinformatic analysis and chromatin immunoprecipitation. Enzyme-linked immunosorbent assay was performed to measure the concentration of inflammatory cytokines. Results: We found that almost all CTRPs were significantly increased in primary human macrophages after differentiation from peripheral blood mononuclear cells. In particular, CTRP1 was further up-regulated upon exposure to oxidized low-density lipoprotein (oxLDL) in a peroxisome proliferator-activated receptor (PPAR)-dependent manner. Chromatin immunoprecipitation also confirmed the presence of PPAR-γ in the CTRP1 promoter after oxLDL treatment. Stimulation of CTRP1 led to markedly enhanced secretion of pro-atherogenic factors, including MCP-1, TNF-α, IL-1β, and IL-6, whereas oxLDL-induced inflammatory cytokine production was significantly attenuated after the treatment with CTRP1 neutralizing antibody. Conclusions: These data suggest an essential role of CTRP1 in linking dysregulation of lipid metabolism and inflammatory responses in macrophages.